E-learning: Revolusi Pembelajaran Masa Kini untuk Masa Depan yang Cerdas - Nurhaliza Nurhaliza; Rayyan Firdaus (Institut Teknologi dan Bisnis (ITB) Semarang, 2024)
With the development of technology now raises a variety of learning methods. One of them is the learning method using e-learning. This learning method also developed rapidly when the covid-19 period was rampant where people could not leave the house to do learning. So that e-learning which is an online application or web becomes the choice of many teachers. Because in that place we can learn online there is no need to leave the house to meet directly with other people. E-learning is also one of the developments in management information systems in Indonesia.